2019
DOI: 10.1002/hed.25761
|View full text |Cite
|
Sign up to set email alerts
|

The role of the T‐N tract in advanced stage tongue cancer

Abstract: Background We investigated the role of the soft tissue tract between the primary tumor and the neck lymph nodes, the “T‐N tract,” in patients with tongue squamous cell carcinoma at an advanced stage. Methods We performed a compartmental tongue surgery in 233 patients. Cumulative incidence of relapses and overall survival curves were compared by T‐N tract involvement. Multivariate Cox proportional hazards models were used to assess the independent role of T‐N tract. Results At 4 years of follow‐up, patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 48 publications
0
45
2
Order By: Relevance
“…The metastasis of the lymph nodes of the floor of the mouth is difficult to observe and diagnose [4]. As a result, it has been proposed that the radical dissection of tongue cancer should contain both the primary lesions and possible pathways of metastasis, including the partial suprahyoid muscle groups and the lymphatic, neurovascular, and glandular tissues [5,7,8]. In this study, we resected the primary lesions and partial suprahyoid muscle groups in all cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The metastasis of the lymph nodes of the floor of the mouth is difficult to observe and diagnose [4]. As a result, it has been proposed that the radical dissection of tongue cancer should contain both the primary lesions and possible pathways of metastasis, including the partial suprahyoid muscle groups and the lymphatic, neurovascular, and glandular tissues [5,7,8]. In this study, we resected the primary lesions and partial suprahyoid muscle groups in all cases.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the thoroughness of the resection in the case of tongue cancer is of particularly importance. It has been recently suggested that the upper lingual muscle groups, such as the genioglossus muscle, geniohyoid muscle, mylohyoid muscle, and/or anterior belly of digastric muscle should also be resected in the radical resection to reduce the possibility of recurrence [5,7,8]. However, defects in the mouth floor and submandibular region post-operation result in the creation of a large unused space, leading to complications such as submandibular wound infection and oral fistula, thereby prolonging the recovery period of the patients and seriously affecting their prognosis [7,9].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the tumor cells can move longitudinally along the path with the least resistance [19]. As a result, some scholars have proposed that the radical dissection of tongue cancer should contain primary lesions and all possible pathways of metastasis, including suboral and partial suprahyoid muscle groups, lymphatic, neurovascular and glandular tissues [5,7,8]. However, this operation method could leave extensive dead cavity in the floor of the mouth and submandibular region, which may lead to submental and submandibular infection and fistula.…”
Section: Discussionmentioning
confidence: 99%
“…However, this operation method could leave extensive dead cavity in the floor of the mouth and submandibular region, which may lead to submental and submandibular infection and fistula. The wound healing process was subsequently affected and the postoperative submandibular shape was depressed obviously [7,9]. Bar graph illustrated the differences of LEFS between the experimental and the control groups…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation